Farmers' attitude analysis on beneficiaries of field and horticultural crops under the farmer first program (FFP) in Khordha district of Odisha - Monikarani , Pradhan; Sarbani , Das; Bibuthi , Prasad Mohapatra; Abhiram , Dash; Khitish , Kumar Sarangi (Plant Science Today, 2025)
This study investigates the attitudes of 148 beneficiaries (77 crop-based, 71 horticulture-based) of the farmer FIRST programme (FFP) in Khordha district, Odisha, using a validated Likert-scale instrument and ex-post facto design. Results showed that 55.8 % of crop-based and 66.2 % of horticulture-based farmers held favourable attitudes toward the programme, with 25.97 % and 14.09 % respectively having a highly favourable outlook. Weighted Mean Scores for core dimensions highlight strong endorsement of participatory decision-making (WMS: 3.87 for crops, 4.14 for horticulture), improved productivity (WMS: 3.66 and 4.10) and programme relevance (WMS: 3.70 and 4.09), affirming FFPs’ positive impact on farm confidence and researcher-farmer collaboration. However, notable concerns persist regarding equitable benefit sharing, affordability of technologies and inclusion-specifically, scores for farm women and landless inclusion (WMS: 3.57 crop, 3.68 horticulture) and low ratings for benefit distribution and communication (WMS: ~1.7 for both groups). Regression analysis identifies education, mass media use, annual income, cosmopoliteness and self-esteem as significant predictors influencing farmer attitudes, accounting for 61-69 % of attitude variation (Adjusted R2 = 0.62–0.61). Practical implications include the need for targeted outreach to marginalised farmers, affordable technology solutions and inclusive extension strategies to maximise FFPs’ impact. These results reinforce participatory extension as a driver of empowerment, innovation and sustainable agricultural development in diverse, transitioning rural contexts.